New trends in the staging of historical works (On the example of Surkhandarya regional musical drama theater) - Faxriddin Abduvohidov (Zien Journals, 2021)
The article discusses the scenic interpretation of the image of Hakim at-Termezi, who is considered one of the leading medieval scholars of Maverannahr, who made an invaluable contribution to the development of world science, in particular, to Islamic teachings and created works containing “sahih” hadiths in their structure.
Keywords: theater; dramaturgy; theme; genre